Factors Related to Decisions to Extract or Retain At-risk Teeth - John J. Warren, DDS, MS; Jed S. Hand, DDS, MHSA; Steven M. Levy, DDS, MPH; H. Lester Kirchner, MS (Blackwell Synergy, 2000)
Decisions to extract a tooth may be among the most criticax dentistry. The aim of this study was to prospectively investigate both clinical and nonclinical factors related to decisions to extract or retain teeth in private general dental practice